Comparison of Volumetric and Bead‐Based Counting of CD34 Cells by Single‐Platform Flow Cytometry. Issue 6 (20th February 2019) - Saraiva, Luisa; Wang, Lili; Kammel, Martin; Kummrow, Andreas; Atkinson, Eleanor; Lee, Ji Youn; Yalcinkaya, Burhanettin; Akgöz, Muslum; Höckner, Jana; Ruf, Andreas; Engel, Andrea; Zhang, Yu‐Zhong; et al.
Abstract : Background: Over 2, 000 people a year in the United Kingdom need a bone marrow or blood stem cell transplant. It is important to accurately quantify the hematopoietic stem cells to predict whether the transplant will be successful in replenishing the immune system. However, they are present at low frequency, which complicates accurate quantification. The current gold standard method is single‐platform flow cytometry using internal reference counting beads to determine the concentration of CD34 cells. However, volumetric flow cytometers have the ability to measure the acquisition volume, which removes the need for reference beads for calculation of cell concentrations. Method: In this study, we compared both methods for calculating CD34 cell concentrations in volumetric cytometers, using either the volume reading or the number of reference beads for calculation. In addition, the uncertainty of measurement for each method was estimated. Results: The results show that both methods have similar uncertainties of measurement. Regression analysis showed low to no statistical difference in CD34 cell concentrations obtained with each method. Conclusions: Overall, this study suggests that the volumetric method is a valid approach but that the adoption of this technology may be hindered without some form of external calibration of volume readings to increase confidence in the measurement. © 2019 The Authors. Cytometry Part B: Clinical Cytometry published by Wiley Periodicals, Inc. on behalf of International Clinical Cytometry Society.